Pembiasaan Doa Wudhu sebagai Upaya Menanamkan Karakter Religius Anak di TPQ Miftakhul Huda Keboananom Gedangan - Pratiwi Fadia Sholihah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
This community service activity aims to instill religious values in the students at TPQ Miftakhul Huda by establishing the habit of praying before and after wudu, as an effort to transform worship practices from mere physical routines into profound spiritual experiences. Using the Asset-Based Community Development (ABCD) approach, this program is carried out through five main stages: discovery, dream, design, define, and do. The results of the activity indicate that through intensive demonstration and practical guidance, the students experienced significant improvement in discipline, awareness of maintaining purity, and moral responsibility as manifestations of Muslim character from an early age. Integrating prayer into the wudu practice has proven effective as an educational tool in building the foundation of faith from an early age, or the “golden age.” The synergy between the student team, educators, and the utilization of institutional facilities proved effective in establishing operational standards for character education that comprehensively integrate physical, mental, and theological aspects. Thus, the practice of wudu prayer serves as a strategic educational tool in strengthening children’s foundational faith during the golden age amidst the challenges of shifting global values.